Writing strategies for the common core integrating reading comprehension into the writing process, grades 6-8 - Wolfe, Hillary (Mankato, MN Maupin House by Capstone Press, 2014)
Middle-school students must be able to write explanatory/informational, argument, and narrative genre pieces and respond to literature, both for standardized tests and, more importantly, real-world writing. With a balanced literacy approach, Wolfe provides core instruction, teaching strategies, and mini-lessons on these text types, each of which can be delivered in a four- to six-week time period. Each mini-lesson
English
a gift from book africa
1 2 13
Keywords: English language -- Composition and exercises -- Study and teaching (Middle school) -- United States; English language -- Composition and exercises -- Study and teaching (Middle school); Language arts (Middle school) -- Standards -- United States